Machine Injury Prediction by Simulation Using Human Models (0111a15c-4251-44e2-bc90-9d29854de8ad) - Dean H. Ambrose (The National Institute for Occupational Safety and Health (NIOSH), 2003)
This paper presents the results of a study using computer human modeling to examine machine appendage speed. The objective was to determine the impact of roof bolter machine appendage speed on the likelihood of the operator coming in contact with. A contact means two or more objects intersecting or touching each other, e.g., appendage makes contact with the operator?s hand, arm, head or leg. Incident investigation reports do not usually contain enough information to aid in studying this problem and laboratory experiments with human subjects are also not feasible because of safety and ethical issues. As an alternative, researchers developed a computer model approach as the primary means to gather data. By simulating an operator?s random behavior and machine?s appendage velocity, researchers can study potential hazards of tasks where it is not possible to perform experiments with human subjects. Analysis information is helpful to the mining industry in terms of making recommendations that reduce the likelihood that roof-bolter operators experience injury due to contact with a moving boom. Data analysis of roof bolter simulations show that the virtual-operator?s response time has little effect on the number of contacts experienced. Based on frequency and cross-tabulation, regardless of other variables, contact incidents were always greater when the boom was moving up, were always greater on the palm, and were always greater for the boom part of the machine. Also, regardless of boom speed, the 25th-percentile-sized operators experienced more contacts than did other operator sizes. Furthermore, regardless of boom speed, the 152-cm mine seam experienced more contacts than did other seam heights tested. Results of a survival analytic approach suggest that controlling the boom speed is the most important factor in determining the risk of an operator making contact. Based on the data collected, boom speed greater than 41 cm/s results in a substantial increase in risk to the roof bolter operator and should probably be avoided. At speeds less than or equal to 25 cm/s are associated with a more modest relative risk, which represents an acceptable level of risk. Also, at speeds between 25 and 41 cm/s, there could be a particular boom speed in this range at which a significant inflection point in the relative risk estimates occurs. Based on the results, this issue needs to be addressed by future research.